2021
DOI: 10.31236/osf.io/nfjqv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Day-to-day associations between sleep and physical activity: a set of person-specific analyses in adults with overweight and obesity

Abstract: The objective of the present study was to estimate whether physical activity (i.e., step counts) on one day was associated with both sleep quality (i.e., sleep efficiency) and quantity (i.e., total sleep time) the following night and to examine to what extent sleep on one night was associated with physical activity the next day. We collected data continuously with a Fitbit Charge 3 among 33 young adults with overweight and obesity participating to a weight management program. A total of 7094 days and nights we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…With respect to our hypotheses, 71 investigated a number of these that we relied on in forming our a priori hypotheses in Subsection “A Priori Hypotheses.” True to our exploratory goals, these are broad in scope and do not specify exact quantities, but rather directions (e.g. increasing or introducing X causes Y to decrease).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…With respect to our hypotheses, 71 investigated a number of these that we relied on in forming our a priori hypotheses in Subsection “A Priori Hypotheses.” True to our exploratory goals, these are broad in scope and do not specify exact quantities, but rather directions (e.g. increasing or introducing X causes Y to decrease).…”
Section: Methodsmentioning
confidence: 99%
“…increasing or introducing X causes Y to decrease). Rather, we created our a priori hypotheses based on both the findings of 71 and our own experiences and reflections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing research using EMA, however, has been criticized for reducing the richness of data in order to conduct traditional statistical approaches (e.g., linear regression, multilevel modeling; [ 21 ]) for generalizing relationships across the sample. Few studies to date have explicitly demonstrated evidence for heterogeneity in within-person associations specific to physical activity [ 22 , 23 ], which were limited to quantitative characteristics of performed physical activity (e.g., duration, intensity, steps per day) that influence physiological adaptations. Beyond that, experiential factors must be accounted for when assessing person-specific associations, as contemporary models and theories in exercise psychology [ 24 27 ] identify affective and evaluative responses arising from physical activity as determinants of future intentions and behavior, in general.…”
Section: Introductionmentioning
confidence: 99%